A Literary and Socio-historical Comparison between the Prayers of Esther (LXX) and Judith - Swart, G.J. (Gerhardus Jacobus), 1955- (University of Pretoria, 2013)
Dissertation (Magister Artium (Ancient Languages and Culture))--University of Pretoria, 2006.